Participation of Learning Citizens in Learning Success in the Package C Program at PKBM Kartini, Tempurejo District, Jember Regency - Meilianti, Fina; Imsiyah, Niswatul; Purnamawati, Frimha (Learning Community : Jurnal Pendidikan Luar Sekolah, 2024)
The aim of the study was to determine the participation of learning residents in the success of learning the Package C program at PKBM Kartini. The research informants were determined using the Purposive Sampling technique, in which the learning residents and tutors of the Paket C program were key informants, while institutional managers were supporting informants. Data collection was carried out using interview techniques, observation and documentation. The resulting data is data in the form of narrative and analyzed using the data analysis model of Miles and Huberman starting with data collection, data reduction, data presentation and data verification. The results of the study show that there is participation of learning citizens in the learning process, but each learning citizen has different learning participation. Contributive participation in attendance and asking questions in learning is different, but has initiative participation to ask for additional material or questions to be studied. The different participation of learning residents is because on average the learning residents are already married and have jobs so it is difficult to manage time. With this participation, it will certainly affect learning outcomes